Trends Towards Enhanced Rates and Sex Parity in HPV Vaccination in Croatia (2016–2023) - Lucija Raic; Ivana Pavic Simetin; Emanuel Bradasevic; Antea Jezidzic; Tatjana Nemeth Blazic; Tamara Poljicanin (Vaccines)
Background/Objectives: Human papillomavirus (HPV) is a recognized cause of cervical cancer and is associated with several other malignancies, including those affecting the vagina, vulva, anus, penis, and head and neck. The introduction of the HPV vaccine has enabled the prevention of HPV-related cancers. This study aimed to determine the HPV vaccination coverage and examine trends in HPV vaccination in Croatia from 2016 to 2023 in the context of the national vaccination program. Methods: This retrospective study analyzed the aggregated school doctors’ data from 2016 to 2023. HPV vaccination coverages within the 2000–2008 birth cohorts were assessed based on the number of doses administrated, sex, and vaccination schedule, while for the trend analysis joinpoint regression was used. The vaccination coverage between sexes was tested using the chi-square test for trends and their ratio was calculated. Results: The HPV full-dose vaccination coverage increased significantly among the observed birth cohorts, from 4.49% in 2000 to 36.88% in 2008, with an APC = 33.97 and 95% CI: 29.37–42.43 (females from 7.74% to 44.98%, males from 1.44% to 29.14%). The highest recorded vaccination coverage was in the one-dose category (2008 female—52.78%). The vaccination coverage of females was significantly higher than that of males (the chi-square for the linear trend = 659.59, p < 0.001) and the female–male ratio decreased from 5.39 in 2000 to 1.54 in 2008. Conclusions: In Croatia, HPV vaccination coverage has increased since the introduction of the national HPV vaccination program. This positive trend was present in both sexes, and the rate ratio between female and male cohorts decreased.